SOSIALISASI PENYUSUNAN RENCANA PEMBANGUNAN JANGKA MENENGAHKAMPUNG (RPJMK) - Romualdus Turu Putra Maro Djanggo; Asrudi Asrudi; Wayrohi Meilvidiri (Musamus Journal of Economics Development, 2019)
This devotion is in the form of socialization to the village officials related to the preparation of the village medium-term development plan. The objectives achieved in this service are to provide insight or knowledge on the importance of information from the beginning of the process of drafting the village Medium Term Development plan and management; Provide knowledge on the preparation and preparation of the village's medium-term development plan; and provide the ability to prepare the development plan of medium-term village. The methods used by this devotion are lectures, and questions answered. The material provided at the time of socialization is the preparation material for the medium-term development plan. The results of discussions with the new living village apparatus, after following the socialization of the establishment of the village medium term development plan, village apparatus and society began to understand that the importance of the procedure to prepare the term development plan Middle of the village and the importance of society in the involvement to develop a medium term development plan Kampung, so that the program in the community already understand it. Overall it is concluded that this activity goes according to good planning and expectation. Keywords: effectiveness, work, head of village.